Planning better health - New South Wales. Department of Health; NSW Health ([North Sydney, NSW] : NSW Dept. of Health, 2004)
Describes the rationale and method of restructuring the public health system in New South Wales, including the combining of 17 area health services into 8 larger services.
Booklet: Planning better health: background information (July 2004 ; SHPN (COM) 040172) -- Sheets: Planning better health - overview -- Area Health Services for NSW -- Northern Sydney/Central Coast Area Health Service -- Western Sydney Area Health Service -- South Western Sydney Area Health Service -- South Eastern Sydney/Illawarra Area Health Service -- North Coast Area Health Service -- Greater Western Area Health Service -- Greater Southern Area Health Service -- Hunter/New England Area Health Service.
Title from folder cover.
Keywords: Public health -- New South Wales; Health services administration -- New South Wales; Health planning -- New South Wales